PERAN YAYASAN “SAMIN” DALAM PENCEGAHAN DAN PENANGANAN KEKERASAN ANAK DALAM KELUARGA (Kasus Peran Yayasan “SAMIN” dalam Pencegahan dan Penanganan Kekerasan Anak dalam Keluarga di Kabupaten Sleman, D.I.Y) - Nadya Tamara Dewaanjani; Sudarsana Sudarsana (Universitas Sebelas Maret (UNS), 2020)
Family is one of the social institutions in the community. Family is also a place for children to acquire mental coaching and personality formation. The family has a considerable role and function on the development and future of the child. However, in fact the violence of children in the family often occurs, such as violence involving fathers, mothers and other siblings. Lack of knowledge and insight related to parenting, growth and development of children is one factor in the occurrence of violence against children. From various cases of child violence, one of NGO named Yayasan SAMIN that cares about child issues to make efforts to prevent and treat child violence in the family. This research aims to know 1) how the role of Yayasan SAMIN in the prevention and handling of child violence in the family, 2) How to form the prevention and handling conducted by the Yayasan SAMIN against Child abuse cases in Family. The results of this study show that 1) Yayasan SAMIN has been explaining its role in the prevention of child violence against parents and the treatment of child abuse victims in families, 2) The prevention of child violence by parents is socialization, campaigning, and KIE (communication, information, education). The form of treatment of victims of violence is with mentoring.